US anatomy of the shoulder: Pictorial essay - Precerutti, M. (Elsevier, 2010)
A thorough knowledge of the anatomy of the shoulder is essential for the assessment of its condition. The purpose of this article is to provide a useful tool for the ultrasound (US) study of this joint. The shoulder girdle and upper arm are made up of a number of muscles and tendons: rotator cuff (supraspinatus, infraspinatus, teres minor and subscapularis), humeral biceps, deltoid and pectoral muscles, which can all be evaluated at US examination. Various and complex capsular ligamentous structures contribute to the stability of the shoulder, but only a few can be adequately evaluated by US and will therefore receive particular attention. Numerous serous bursae are situated among muscles, skin, subcutaneous tissues, joint capsule structures and bones to prevent friction and they can be evaluated by US only in the presence of pathologies. Subacromial-subdeltoid and subcoracoid bursa are most frequently involved and will therefore be described in detail. There are furthermore nerves and vessels providing the various components of the shoulder with innervation and vascularization, and they can also be studied by US. The shoulder girdle (humerus, scapula, clavicle and sternal manubrium) is situated in the deep layers; only the cortex of the bone can be seen at US as a continuous hyperechoic line. For a better understanding of the location and relationship between the structures which can be studied by US, magnetic resonance imaging (MRI) can be carried out as this method provides a wider and more complete view of the structures.